Dos respuestas desde la estética a la pregunta por la filosofía, a través de Heidegger y Deleuze - Rampérez Alcolea, Fernando (Logos. Anales del Seminario de Metafísica, 2009)
An analysis of the notion of philosophy in Heidegger and Deleuze allows us to verify how both are taken to an aesthetic exposition, to a poetic conception of the language or the creativity, in order to characterize to the philosophy. The distance between both resides, however, in the dissatisfaction which inevitably they undergo the hopes of Heidegger when depositing them in the poetic thing, whereas Deleuze compares the philosophical task and aesthetic when consisting the both of sense production.
Keywords: Aesthetics; Phylosophy; Hope; Concept; Sense; Heidegger; Deleuze